In vitro reduction of Streptococcus mutans biofilm on silver nanoparticle-modified resin composite - Neves, Patricia Bolzan Agnelli das; Souza, Clovis Wesley Oliveira de; Pizzolitto, Elisabeth Loshchagin [UNESP] (My University, 2014)
Introduction: Currently, new methods to reduce biofilm formation on biomaterials are very studied, for example the use of silver nanoparticles, which were bactericidal. However, there are few studies investigating the benefits of these particles in dental restorative materials. Objective: This study aimed to compare in vitro the Streptococcus mutans biofilm formation on conventional light-cured composite resin with that on experimental light-cured composite resin, modified with silver nanoparticles. Material and methods: Discs were produced with either conventional resin (control group) and resin modified with different concentrations of silver nanoparticles, 0.1%, 0.3% and 0.6 % wt. (groups 1, 2 and 3, respectively). The samples were incubated in bacterial suspension (S. mutans) enriched with 20% sucrose to promote biofilm growth on the surfaces. Incubation times were 1, 4 and 7 days. After each period, adherent biofilms were disaggregated by ultrasound. Then, the numbers of viable cells recovered from the biofilms were counted through the serial dilution method. A morphological analysis of biofilm was also performed by Scanning Electron Microscopy. The data were subjected to Anova and Tukey’s test (α = 0.05). Results: The number of viable cells was statistically lower in groups 2 and 3 than in group 1 and control group, after the three incubation periods, without statistical difference between groups 2 and 3. The number of viable cells was statistically lower in group 1 than in control group, after 4 and 7 days of incubation. Conclusion: Resins modified with silver presented reduction of S. mutans biofilm on their surfaces, according to the conditions of this study.
Keywords: Biofilms; Streptococcus mutans; Composite resins; Nanoparticles